PARTAI POLITIK: SUATU TINJAUAN TEORITIS - Agus Riyanto (SPEKTRUM, 2004)
Abstract This article discribed political party theorizing that were early history of development, function, and typology of political parties. The existence of political party was central phenomena on political way of the state. Political partay could push the state to more democratic or vis a vis authoriterian. That condition was influenced by internal condition, party system and ideological distance between political parties, whether centripetal or centrifugal types. Key Word: political party, power, people, articulation